Method for optimizing the mix of anticorrosive concrete

CN122967862APending Publication Date: 2026-10-23TIANJIN JIANCHENGJIYE GRP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611437781.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-16
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

因此,现有技术中存在混凝土不同深度区域的配比与其实际腐蚀介质侵入作用不匹配的技术问题

Benefits of technology

[0016]本发明的有益效果在于:在选择当前区域的配比时,将介质接触面与当前区域之间已经确定配比的各混凝土层一并制成组合试件,并使各混凝土层具有对应区域的厚度。腐蚀介质到达当前区域前,需要依次通过这些混凝土层。因此,当前区域候选配比的试验结果同时反映了位于当前区域与介质接触面之间的各混凝土层的配比和厚度对介质迁移的影响,避免使用单一材料性能指标代替不同深度区域的实际介质作用。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122967862A_ABST
    Figure CN122967862A_ABST
Patent Text Reader

Abstract

The application provides an anti-corrosion concrete proportioning optimization method, and relates to the technical field of concrete materials. The application obtains an exposure initial age of concrete in single-face contact with a corrosive medium, a change of a medium concentration at a medium contact surface with time, an exposure duration, thicknesses of regions, and a candidate proportioning, prepares a combined test piece from the medium contact surface inwards by region, makes a current region adopt the candidate proportioning, makes each region between the current region and the medium contact surface adopt a selected proportioning, and each concrete layer has a corresponding region thickness; a single-face corrosive medium intrusion test is implemented according to the above exposure conditions, a proportioning is selected according to an intrusion depth in a current region concrete layer, and each region proportioning and thickness are output. The proportioning selection of each region can correspond to a medium migration path, an exposure time, and a concrete age at the same time, and a situation that a region proportioning does not match actual corrosive medium action is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of concrete materials technology, specifically to a method for optimizing the mix proportion of corrosion-resistant concrete. Background Technology

[0002] When concrete is exposed to a corrosive medium on only one surface, the medium migrates from the contact surface into the concrete. As the migration distance increases, the duration and degree of contact with the corrosive medium at different depths vary; these differences further increase when the medium concentration at the contact surface changes over time. Mix design is developed for this single-sided exposure condition to control the intrusion of corrosive media and to provide a basis for material configuration at different thicknesses of the concrete.

[0003] In the prior art, Chinese Patent Publication No. CN103992076A discloses a concrete mix design method based on chloride ion intrusion resistance and strength requirements. This method determines the concrete's strength parameters, chloride ion diffusion coefficient, and age decay coefficient, establishes calculation models for the water-cement ratio, chloride ion diffusion coefficient, and age decay coefficient, and calculates the water-cement ratio and mineral admixture dosage accordingly to obtain the mix proportion of concrete per unit volume.

[0004] The above method calculates the mix proportion using the same concrete performance indicators, and the resulting mix proportion is applied to the entire concrete thickness. When concrete is exposed to a corrosive medium with a concentration that varies over time only from one surface, the concrete thickness traversed before the medium reaches different depths varies, and the time it takes to reach each location also differs. Therefore, the overall performance indicators of the same mix proportion cannot directly reflect the actual medium intrusion process at each depth. Consequently, the selected mix proportion is inconsistent with the medium's effect at the corresponding depth. Therefore, the existing technology suffers from a technical problem where the mix proportion of concrete at different depths does not match the actual corrosive medium intrusion. Summary of the Invention

[0005] The technical problem to be solved by this application is: when a corrosive medium with a concentration that changes over time is in contact with a single side, the mix proportions of concrete at different depths correspond to the thickness of the concrete that the corrosive medium passes through before reaching that area and the actual process of medium action experienced by that area.

[0006] To address the aforementioned technical problems, this application provides a method for optimizing the mix proportions of corrosion-resistant concrete. This method obtains the initial exposure age of concrete in single-sided contact with a corrosive medium, the change in medium concentration at the contact surface over time during exposure, the exposure duration, the thickness of at least two regions arranged sequentially along the medium migration direction, and at least two candidate mix proportions.

[0007] Starting from the contact surface with the medium, each region is sequentially designated as the current region. Composite specimens are prepared using each candidate mix design. The composite specimen is formed by sequentially casting the concrete layers corresponding to the current region and the regions located between the current region and the medium contact surface, arranged from the contact surface with the medium inwards. The thickness of each concrete layer is equal to the thickness of the corresponding region; the concrete layer of the current region uses the corresponding candidate mix design, while the concrete layers located between the current region and the medium contact surface use the selected mix design for the corresponding region.

[0008] Each composite specimen was cured to the initial exposure age. A single-sided corrosion medium intrusion test was conducted on each composite specimen from the medium contact surface within the exposure period, based on the change in medium concentration over time. After the test, the intrusion depth of the corrosive medium into the concrete layer of the current area of ​​each composite specimen was measured. The candidate mix proportion corresponding to the composite specimen with the smallest intrusion depth was selected as the mix proportion for the current area. After the above treatment was completed in each area, the mix proportion and thickness of each area were output.

[0009] Optionally, before outputting the mix proportions and thicknesses of at least two regions, the current region is determined sequentially from the at least two regions in the order of moving inward from the medium contact surface along the medium migration direction. For each candidate mix proportion, a composite specimen is prepared consisting of concrete layers corresponding to at least two regions. The thickness of each concrete layer is equal to the thickness of the corresponding region. The concrete layer of the current region uses the candidate mix proportion, while the concrete layers of other regions use the selected mix proportion of the corresponding region. Each composite specimen is cured to the initial exposure age, and a single-sided corrosion medium penetration test is conducted from the medium contact surface within the exposure time according to the aforementioned change in medium concentration over time. After the test, the penetration depth in the concrete layer of the current region of each composite specimen is measured, and the candidate mix proportion corresponding to the composite specimen with the smallest penetration depth is selected to replace the selected mix proportion of the current region.

[0010] Optionally, the thickness of each region is obtained through a single-sided corrosion medium penetration test on a full-thickness specimen. Specimens are prepared using each candidate mix design, and the thickness of each specimen along the medium migration direction is equal to the thickness of the concrete to be designed along the medium migration direction. Each specimen is cured to the initial exposure age, and a single-sided corrosion medium penetration test is conducted within the exposure time according to the change of medium concentration over time. At least two detection times are set within the exposure time, and the penetration depth of each specimen is measured at each detection time. The medium contact surface, the surface opposite the medium contact surface, and the non-overlapping penetration depth positions are used as region boundaries. The boundaries of each region are arranged along the medium migration direction, and the distance between every two adjacent region boundaries along the medium migration direction is taken as the thickness of a region.

[0011] Optionally, at least two testing times correspond to different specimen groups, and each specimen group includes specimens prepared using each candidate formulation. When any testing time is reached, the single-sided corrosion medium penetration test of the specimen group corresponding to that testing time is terminated, and the penetration depth of each specimen in that specimen group is measured; the specimen groups that have not yet reached their corresponding testing times continue to undergo the single-sided corrosion medium penetration test.

[0012] Optionally, a control specimen is prepared for each composite specimen. The number of concrete layers in the control specimen is equal to the number of concrete layers in the corresponding composite specimen, and the mix proportion and thickness of each concrete layer in the control specimen are equal to the mix proportion and thickness of the concrete layers at the same location in the corresponding composite specimen. Each composite specimen and its corresponding control specimen are placed in the same curing environment and cured until the initial exposure age. During the media immersion test of the composite specimens, the control specimen remains in the same curing environment and does not come into contact with the corrosive medium; the temperature, exposure time, sealing method of the surfaces other than the media contact surface, and sampling time are the same for both specimens. The media contact surface of the control specimen is in contact with a volume of water equal to the corrosive medium, and this water does not contain the corrosive ions to be measured. After the test, samples are continuously taken from the same location and of the same thickness along the direction of media migration from both specimens, and the corrosive medium content of each sample is compared according to the uncertainty judgment rules of the detection method to determine the immersion depth.

[0013] Optionally, the interface between adjacent concrete layers in each composite specimen is perpendicular to the direction of medium migration. Adjacent concrete layers are poured sequentially from the medium contact surface inward along the direction of medium migration, with the next concrete layer poured on the surface of the previous concrete layer away from the medium contact surface before the previous concrete layer initially sets.

[0014] Optionally, each candidate mix corresponds to at least two combined specimens, and the maximum penetration depth among the combined specimens corresponding to the same candidate mix is ​​taken as the penetration depth of that candidate mix, so that the comparison of candidate mixes includes the deepest penetration result observed in each replicate specimen of that mix. During the single-sided corrosive medium penetration test, the surfaces of each combined specimen except for the medium contact surface are sealed. During the exposure time, the medium contact surface of each combined specimen is continuously in contact with the corrosive medium, and the concentration of the corrosive medium in contact with the medium contact surface of each combined specimen is adjusted according to the change in medium concentration over time.

[0015] Optionally, the types of constituent materials used in each candidate formulation are the same, but the unit volume of at least one constituent material differs between any two candidate formulations.

[0016] The beneficial effects of this invention are as follows: When selecting the mix proportion for the current region, each concrete layer with a predetermined mix proportion between the medium contact surface and the current region is prepared as a composite specimen, and each concrete layer has the thickness corresponding to the region. Before reaching the current region, the corrosive medium needs to pass through these concrete layers sequentially. Therefore, the test results of the candidate mix proportion for the current region simultaneously reflect the influence of the mix proportion and thickness of each concrete layer located between the current region and the medium contact surface on medium migration, avoiding the use of a single material performance index to replace the actual medium action at different depths.

[0017] Furthermore, the present invention conducts experiments based on the actual exposure start age, exposure duration, and changes in medium concentration over time. When the corrosive medium reaches the current area after passing through each concrete layer located between the current area and the medium contact surface, the age of the concrete layer in the current area has increased to the age when the medium reached the area. Therefore, the experiment can simultaneously reflect the influence of changes in concrete material properties with age and changes in medium exposure time with depth.

[0018] Furthermore, this invention directly selects candidates based on the penetration depth corresponding to each candidate mix proportion, without needing to establish a mix proportion scoring function or set a mix proportion qualification threshold. The comparison of corrosive medium content uses detection methods to verify the repeatability requirements and expanded measurement uncertainty given in the records or test reports, without setting separate penetration judgment values. Control specimens and composite specimens are subjected to the same temperature, exposure time, non-media contact surface sealing method, and sampling time, and are compared at corresponding locations to eliminate the influence of the original media components in the constituent materials and the non-corrosive media exposure conditions on the measurement results. When processing composite specimens containing all areas of concrete layer zone by zone again, only the mix proportion of the current zone is changed each time, while the mix proportions of other zones remain unchanged. The measured penetration depth determines whether to replace the mix proportion of the current zone. Attached Figure Description

[0019] To more clearly illustrate the technical solutions of the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0020] Figure 1 A flowchart of a method for optimizing the mix proportion of corrosion-resistant concrete provided in an embodiment of the present invention.

[0021] Figure 2 This is a schematic diagram illustrating the determination of the region boundary based on the intrusion depth at different detection times, as provided in an embodiment of the present invention.

[0022] Figure 3This is a schematic diagram of the cross-sectional structure of the combined specimen corresponding to the current region along the medium migration direction, provided in an embodiment of the present invention.

[0023] Figure 4 This is a schematic diagram showing continuous sampling of the combined specimen and the control specimen at the same location, as provided in an embodiment of the present invention.

[0024] In the figure: 1. Corrosive medium; 2. Direction of medium migration; 3. Selected area concrete layer on one side of the medium contact surface; 4. Subsequent selected area concrete layer; 5. Current area concrete layer; 6. Medium contact surface; 7. Surface opposite to the medium contact surface; 8. Full thickness specimen; 9. Penetration depth location; 10. Area thickness; 11. Combined specimen; 12. Control specimen; 13. Sample; 14. Corresponding position; 15. Remote sample; 16. Penetration depth. Detailed Implementation

[0025] To enable those skilled in the art to better understand the present application, the present application will be further described in detail below with reference to the accompanying drawings and specific embodiments. Obviously, the described embodiments are only a part of the embodiments of the present application, and not all of them. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present application. The following numerical values ​​are used to illustrate the operation process and are not intended to limit the scope of protection.

[0026] like Figure 1 As shown, Figure 1 The steps S1, S2, S3, and S4 are shown in sequence according to the overall operation order. S1 obtains the exposure conditions, thickness of each region, and candidate mix proportions; S2 determines the current region and prepares the composite specimen; S3 performs a single-sided corrosion medium intrusion test, measures the intrusion depth, and selects the mix proportion for the current region; S4 outputs the mix proportions and thicknesses of each region. The sequential processing of each region in S2 and S3 is described in the corresponding text steps. Figure 1 The internal repeating paths of this area-by-area processing are not drawn separately.

[0027] S1, obtain the initial exposure age of the concrete in single-sided contact with the corrosive medium, the change of medium concentration at the medium contact surface over time during exposure, the exposure duration, the thickness of at least two regions arranged sequentially along the medium migration direction, and at least two candidate mix proportions.

[0028] In step S1, the medium contact surface is the surface of the concrete that directly contacts the corrosive medium. The medium migration direction is from the medium contact surface to the surface opposite it, and the regions are arranged continuously along this direction. It should be understood that the corrosive medium is limited to an aqueous solution with water-soluble ions as quantitative tracers, and the penetration depth is determined by the content of these water-soluble ions. The exposure start age is the time from when the concrete is poured and formed until the start of contact with the corrosive medium; the exposure duration is the time from the start of contact with the corrosive medium until the end of the medium penetration test; the change in medium concentration over time consists of the concentrations within the exposure duration and their corresponding start and end times, which can be obtained from monitoring records at the medium contact surface or from a determined usage process.

[0029] The exposure start age determines the material age of the concrete when it begins to be exposed to the medium. The change in medium concentration over time and the exposure duration together determine the medium conditions applied to the medium-contact surface during the test. The sum of the thicknesses of each region equals the thickness of the concrete requiring mix design along the direction of medium migration and is used to determine the dimensions of each concrete layer in the composite specimen. Candidate mix designs are used to form a control group for the concrete layers in the current region. The above data serve as inputs for subsequent specimen preparation, medium exposure, and mix design.

[0030] The thickness of each region can be directly used as the input to S1, or it can be obtained through a single-sided corrosion medium intrusion test on a full-thickness specimen. When obtaining the thickness through testing, first obtain the total thickness of the concrete along the medium migration direction, and then prepare specimens with that total thickness using each candidate mix design. Cure each specimen to the initial exposure age, and conduct a single-sided corrosion medium intrusion test within the exposure time according to the change in medium concentration over time, setting at least two detection times within the exposure time. At each detection time, measure the intrusion depth of the corresponding specimen. The intrusion depth locations located inside the concrete and not overlapping, the medium contact surface, and the surface opposite the medium contact surface are used as region boundaries. Arrange the region boundaries according to their positions along the medium migration direction, and then define the distance between every two consecutive region boundaries as the thickness of one region.

[0031] When measuring penetration depth requires sampling of the specimen, the same specimen cannot be used simultaneously for two consecutive testing times; otherwise, sampling at the earlier testing time will alter the medium migration path at the later testing time. Therefore, each testing time corresponds to a set of independent specimens, and each set includes specimens prepared using each candidate formulation. Upon reaching any testing time, the medium penetration test for the corresponding set of specimens ends, and the penetration depth is measured. Other sets of specimens that have not yet reached their corresponding testing times continue the medium penetration test.

[0032] like Figure 2As shown, the full-thickness specimen 8 extends along the medium migration direction 2 from the medium contact surface 6 to the surface 7 opposite to the medium contact surface. The dashed lines inside the full-thickness specimen 8 represent the non-overlapping penetration depth positions 9. The medium contact surface 6, the surface 7 opposite to the medium contact surface, and the penetration depth positions 9 together constitute the region boundary. The distance between two adjacent region boundaries along the medium migration direction 2 is the region thickness 10. When two penetration depth measurements are at the same position, only one penetration depth position 9 is retained; when they are at different positions, the corresponding penetration depth positions 9 are retained respectively.

[0033] For example, if the total concrete thickness is 60mm and the sampling thickness is 5mm, the penetration depths of three candidate mix proportions measured on day 30 are 10mm, 5mm, and 5mm respectively, and the penetration depths measured on day 90 are 25mm, 20mm, and 15mm respectively. After removing duplicate locations, 0mm, 5mm, 10mm, 15mm, 20mm, 25mm, and 60mm are used as the area boundaries in sequence, and the resulting area thicknesses are 5mm, 5mm, 5mm, 5mm, 5mm, and 35mm respectively. After completing each pre-set detection time within the exposure duration, the thickness of at least two areas is obtained only if at least one penetration depth location greater than 0mm and less than 60mm is obtained. If all detection results are 0mm, all are 60mm, or no penetration depth location located inside the concrete is obtained, the optional thickness acquisition process ends, and S1 receives the pre-given thicknesses of at least two areas, where the thickness of each received area is greater than 0 and their sum is equal to 60mm.

[0034] S2, starting from the medium contact surface and working inwards, each region is sequentially designated as the current region, and composite specimens are prepared using each candidate mix design. The composite specimen is formed by pouring concrete layers corresponding to the current region and the regions located between the current region and the medium contact surface, arranged in an inward-facing sequence. The thickness of each concrete layer is equal to the thickness of its corresponding region. The concrete layer of the current region uses the corresponding candidate mix design, while the concrete layers located between the current region and the medium contact surface use the selected mix design for their respective regions.

[0035] Specifically, when the first region arranged along the direction of medium migration is taken as the current region, there are no other regions between this region and the medium contact surface. Therefore, the composite specimen only includes the concrete layer of the current region. After the mix design of this region is completed, the next region is taken as the current region, and the newly prepared composite specimen adds the concrete layer corresponding to the previous region. In this manner, for each additional region between the current region and the medium contact surface, the composite specimen adds the concrete layer between that region and the medium contact surface, which has already undergone mix design selection, so that the concrete layers that the corrosive medium passes through before reaching the current region are consistent with the actual arrangement.

[0036] like Figure 3As shown, corrosive medium 1 is located on the medium contact surface side of the composite specimen and enters the composite specimen along the medium migration direction 2. The selected area concrete layer 3, the subsequent selected area concrete layer 4, and the current area concrete layer 5 on the medium contact surface side are arranged sequentially along the medium migration direction 2, with the dimension of each layer along the medium migration direction 2 equal to the thickness of the corresponding area. The selected area concrete layer 3 and the subsequent selected area concrete layer 4 on the medium contact surface side each use the selected mix proportion for their respective areas, while the current area concrete layer 5 uses the candidate mix proportion; the joint surface of adjacent concrete layers is perpendicular to the medium migration direction 2.

[0037] Each candidate mix design uses the same type of constituent materials, and the amount of each constituent material per unit volume of concrete is expressed as the quantity of each constituent material. At least one constituent material per unit volume differs between any two candidate mix designs. Therefore, the experimental differences between candidate mix designs correspond to differences in the quantity of constituent materials used, and the comparison remains unchanged regardless of the addition or removal of material types.

[0038] When casting composite specimens, a mold with height markings along the direction of medium migration was used. The concrete layer on the side of the medium contact surface was poured first, and after reaching the corresponding height mark, it was leveled before pouring the next concrete layer. The next concrete layer was poured on the surface of the previous concrete layer away from the medium contact surface, before the initial setting of the previous layer. The initial setting time of the previous concrete layer was determined using the penetration resistance method of concrete mixtures with the same mix proportions. All layers were cured together after casting; the joint surfaces were not cut, nor were additional bonding materials used to connect the joint surfaces.

[0039] S3. Cure each composite specimen to the initial exposure age. According to the change of medium concentration over time, conduct a single-sided corrosion medium intrusion test on each composite specimen from the medium contact surface within the exposure time. After the test, measure the intrusion depth of the corrosive medium in the current area of ​​the concrete layer of each composite specimen. Select the candidate mix ratio corresponding to the composite specimen with the smallest intrusion depth as the mix ratio of the current area.

[0040] To ensure the corrosive medium enters the composite specimen along its migration direction, after curing, all surfaces of the composite specimens except the medium-contact surface are sealed. The sealing material continuously covers the sides of each concrete layer, the exposed sides of the interlayer bonding surfaces, and the surfaces away from the medium-contact surface. During the test, the medium-contact surface remains in continuous contact with the corrosive medium. When changing the medium concentration, while the medium-contact surface remains covered by the corrosive medium, the medium of the next time period's concentration is added, and the original medium is removed, until the medium in contact with the medium-contact surface reaches the concentration corresponding to the next time period.

[0041] When measuring the penetration depth, the corrosive medium is an aqueous solution containing water-soluble ions that can be quantitatively measured through chemical analysis, and these water-soluble ions are used as the measurement target for the corrosive medium content. Chloride solutions correspond to the content of water-soluble chloride ions, and sulfate solutions correspond to the content of sulfate ions. To distinguish the externally infiltrated corrosive medium from the original components in the constituent materials, a control specimen is prepared for each composite specimen. The number of concrete layers, the mix proportions of each concrete layer, and the thickness of the control specimen are the same as those of the corresponding composite specimen. Both specimens are placed in the same curing environment and cured until the initial exposure age. During the medium penetration test, both specimens are placed under the same temperature conditions, and the surfaces other than the medium contact surface are sealed in the same way; the medium contact surface of the composite specimen is in contact with the corrosive medium, while the corresponding surface of the control specimen is in contact with a volume of water equal to the corrosive medium, which does not contain the corrosive ions to be measured. The exposure time, liquid replacement time, and sampling time are the same for both specimens.

[0042] like Figure 4 As shown, the medium contact surfaces 6 of the combined specimen 11 and the corresponding control specimen 12 are located at the same end, and the current area concrete layers 5 in both specimens have the same mix ratio and thickness. Samples 13 are continuously obtained from the combined specimen 11 and the control specimen 12 within the current area concrete layer 5 at the same position and with the same thickness. The dashed lines indicate the corresponding positions 14 connecting the sample boundaries of the two specimens at the same distance from the medium contact surface 6. The sample with the corrosive medium content greater than that of the corresponding sample in the control specimen 12, and the farthest from the medium contact surface 6, as determined according to the uncertainty judgment rules of the detection method, is the far-end sample 15; the distance from the side of the current area concrete layer 5 facing the medium contact surface 6 to the side of the far-end sample 15 away from the medium contact surface 6 is the penetration depth 16.

[0043] For example, when the corrosive medium is an aqueous sodium chloride solution, the sample is crushed and mixed, and the mass fraction of water-soluble chloride ions is measured by potentiometric titration; when the corrosive medium is an aqueous sodium sulfate solution, the sample is crushed and mixed, and the mass fraction of sulfate ions is measured by ion chromatography. Before formal measurement, a valid method validation record or test report is obtained for the adopted detection method and the concrete sample matrix, which records the limit of detection, limit of quantitation, number of parallel samples, limit of repeatability, report resolution, and expanded measurement uncertainty; the above parameters are the values ​​in the record or report and are not set separately by the mix optimization process. Samples at each location are measured according to the number of parallel samples recorded therein. If the parallel measurement results do not meet the repeatability requirements, resampling and measurement are performed. The quantitative range of the detection method should cover the measurement results of the combined specimen and the control specimen. Results below the limit of quantitation are not used to determine the farthest intrusion sample. The statement in this paper that the corrosive medium content of the combined specimen sample is greater than that of the corresponding control specimen sample means that the reported value of the combined specimen sample minus its expanded measurement uncertainty is still greater than the reported value of the control specimen sample plus its expanded measurement uncertainty; if this relationship is not met, it shall be treated as not greater than.

[0044] Each candidate mix design corresponds to at least two composite specimens. The penetration depth of each composite specimen corresponding to the same candidate mix design within the concrete layer of the current region is determined, and the maximum penetration depth is taken as the penetration depth of that candidate mix design. The penetration depths of each candidate mix design are compared, and the candidate mix design with the minimum penetration depth is selected as the mix design for the current region. Using the maximum penetration depth ensures that the deepest penetration observed in duplicate specimens of the same candidate mix design is included in the mix design comparison, preventing this result from being reduced due to averaging the penetration depths of other duplicate specimens.

[0045] S2 and S3 together constitute the zone-by-zone processing procedure. After the mix ratio selection for the current zone is completed, the next zone is taken as the current zone along the direction of medium migration. In the same zone-by-zone processing procedure, combined specimens are prepared, medium intrusion tests are carried out, and mix ratios are selected until at least two zones have obtained the mix ratios; then S4 is executed. Figure 1 The above-described zone-by-zone processing is represented by two consecutive steps, S2 and S3, without showing the repeated paths between zones individually.

[0046] Before performing S4, the current region can be determined sequentially from at least two regions, following the order of media contact surface inward along the media migration direction. The selected mix proportion for the current region is then adjusted according to the specimen preparation, media penetration test, and penetration depth measurement methods described in S2 and S3. For each candidate mix proportion, a composite specimen consisting of concrete layers corresponding to at least two regions is prepared. The concrete layer of the current region uses the candidate mix proportion, while the concrete layers of other regions use the selected mix proportion for their respective regions. The thickness of each concrete layer is equal to the thickness of its corresponding region. The test is conducted under the same exposure conditions, and the penetration depth within the concrete layer of the current region is measured. The candidate mix proportion corresponding to the composite specimen with the smallest penetration depth is selected to replace the selected mix proportion for the current region before processing the next region, allowing the already occurred mix proportion replacement to participate in the processing of the next region. This optional process is completed before S4. Figure 1 No separate process nodes are set for it.

[0047] S4 outputs the mix proportions and thicknesses of each region. If no further region-by-region processing is performed, the output shows the mix proportions obtained from the initial region-by-region selection; if further region-by-region processing is performed, the output shows the mix proportions of each region after the second processing. The output content is arranged in region order from the medium contact surface inwards, ensuring that the mix proportion of each region corresponds to its thickness.

[0048] The following is an example that follows the above steps. The total thickness of the concrete to be optimized along the direction of medium migration is 90 mm. Existing experimental data divides it into three regions from the medium contact surface inward: a first region, a second region, and a third region, with corresponding thicknesses of 20 mm, 20 mm, and 50 mm, respectively. The initial exposure age is 28 days, the exposure duration is 90 days, and the corrosive medium is a sodium chloride aqueous solution.

[0049] Three candidate mix proportions, M1, M2, and M3, were obtained from S1. Each candidate mix proportion uses the same types of constituent materials. The amounts of each constituent material per cubic meter of concrete are as follows: M1: 160 kg water, 340 kg cement, 40 kg fly ash, 40 kg slag powder, 700 kg fine aggregate, 1080 kg coarse aggregate, and 4.2 kg water-reducing agent; M2: 155 kg water, 300 kg cement, 80 kg fly ash, 60 kg slag powder, 700 kg fine aggregate, 1080 kg coarse aggregate, and 4.6 kg water-reducing agent; M3: 150 kg water, 280 kg cement, 60 kg fly ash, 100 kg slag powder, 700 kg fine aggregate, 1080 kg coarse aggregate, and 5.0 kg water-reducing agent. There are differences in the amounts of constituent materials between any two candidate mix proportions.

[0050] The mass fraction of sodium chloride aqueous solution at the medium contact surface changed over time as follows: 3.0% from the start of exposure until day 30, 5.0% from day 30 to day 60, and 2.0% from day 60 to the end of the test on day 90. The start and end times of each time period were determined by the moment when the combined specimen began to come into contact with the corrosive medium.

[0051] When executing S2, the first region is initially selected as the current region. There are no other regions between this region and the medium contact surface. Single-layer composite specimens with a thickness of 20 mm are prepared using M1, M2, and M3 respectively, with two composite specimens prepared for each candidate formulation. After executing S3, M3 is selected as the first region.

[0052] When the second region is selected as the current region, a two-layer composite specimen is prepared. The first layer facing the medium contact surface is 20 mm thick and uses M3, and the second layer is 20 mm thick and uses M1, M2, and M3 respectively. After selecting M2 for the second region, the third region is selected as the current region. The three-layer composite specimen consists of a first layer with a thickness of 20 mm and using M3, a second layer with a thickness of 20 mm and using M2, and a third layer with a thickness of 50 mm and using M1, M2, and M3 respectively, starting from the medium contact surface inwards.

[0053] Each composite specimen was poured continuously in the sequence described in S2, with the next concrete layer poured before the previous one had initially set. A control specimen was prepared for each composite specimen, with the number of concrete layers in the control specimen equal to that in the corresponding composite specimen. The mix proportions and thicknesses of each concrete layer in the control specimen were equal to those of the concrete layers at the same location in the corresponding composite specimen. Both types of specimens were aged from the molding time of the same pouring batch and cured in the same curing environment for 28 days.

[0054] During S3, both the combined specimen and the control specimen were sealed with an epoxy resin coating in the same manner, except for the media contact surface, and both specimens were placed under the same temperature conditions. The media contact surface of the combined specimen was continuously in contact with a sodium chloride aqueous solution for 90 days, with the concentration of the aqueous solution adjusted according to the aforementioned concentration changes. The control specimen was retained in the same curing environment, and its corresponding surface was continuously in contact with a volume equal to the sodium chloride aqueous solution of prepared water (without added sodium chloride) for 90 days. On days 30 and 60, when adjusting the concentration of the aqueous solution in contact with the combined specimen, the volume of prepared water in contact with the control specimen was simultaneously replaced. Both specimens were simultaneously removed from exposure on day 90, and samples with a thickness of 5 mm were continuously collected at the same location along the media migration direction, starting from the media contact surface.

[0055] Taking a combined specimen using M2 in the second region as an example, the reported mass fraction values ​​of water-soluble chloride ions for four consecutive samples in the second region are: 0.030%, 0.020%, 0.010%, and 0.009% for the combined specimen, and 0.010%, 0.010%, 0.010%, and 0.010% for the corresponding control specimen at the same location. For example, if the expanded measurement uncertainty given in the test report for the 0.020% reported value of the combined specimen and the corresponding 0.010% reported value of the control specimen is 0.002% (in mass fraction), then the expanded measurement uncertainty of the combined specimen is 0.018% minus the reported value of the combined specimen, and the expanded measurement uncertainty of the control specimen is 0.012% plus the reported value of the control specimen. Since 0.018% is greater than 0.012%, it is determined that the corrosive medium content of the combined specimen sample is greater than that of the corresponding control specimen sample. The aforementioned 0.002% is only used to illustrate the judgment process; in actual implementation, the corresponding method is used to verify the expanded measurement uncertainty given in the record or test report.

[0056] All the above results are within the quantitative range of the detection method, and the parallel measurement results meet the repeatability requirements in the method validation record. The reported values ​​of the combined specimens at the first two locations, after subtracting the corresponding expanded measurement uncertainty, are still greater than the reported value of the control specimen plus the corresponding expanded measurement uncertainty. The latter two locations do not satisfy this relationship. Therefore, according to the uncertainty judgment rule, the farthest sample is determined to be a sample between 5mm and 10mm in diameter, and the penetration depth of this combined specimen in the concrete layer of the second region is 10mm. In the third region, using the two combined specimens of M3, none of the samples in the current region satisfy the above greater than relationship, and the penetration depth of both combined specimens is recorded as zero.

[0057] For two combinations of specimens with the same candidate mix, the penetration depth was determined, and the maximum value was taken as the penetration depth of the candidate mix. In the initial zone-by-zone selection, the penetration depths of zones M1, M2, and M3 were 15mm, 10mm, and 5mm, respectively; those of zones M1, M2, and M3 were 15mm, 10mm, and 15mm, respectively; and those of zone M1, M2, and M3 were 5mm, 10mm, and 0mm, respectively. Therefore, the initial zone-by-zone selection results were M3, M2, and M3, respectively.

[0058] Before executing S4, composite specimens containing three concrete zones were prepared using the reprocessing method. Each time, only the candidate mix proportion for the current zone was changed; other zones used the previously selected mix proportion. When processing the third zone, the second zone used M3, which had been replaced in the previous processing. The reprocessing results were: the first zone retained M3; the second zone was replaced by M3 from M2; and the third zone was replaced by M2 from M3. After executing S4, the following mix proportions were output in order from the contact surface inwards: first zone thickness 20mm, mix proportion M3; second zone thickness 20mm, mix proportion M3; third zone thickness 50mm, mix proportion M2.

[0059] Those skilled in the art can implement this application by following the steps disclosed in this application, including concrete specimen preparation, curing, single-sided corrosive medium intrusion test, sampling, and corrosive medium content detection. The above embodiments are used to illustrate the technical solution of this application, and any equivalent substitutions or conventional adjustments that do not depart from the essence of the technical solution of this application are all within the protection scope of this application.

Claims

1. A method for optimizing the mix proportions of corrosion-resistant concrete, characterized in that, include: The exposure start age of concrete in single-sided contact with corrosive media, the change of medium concentration at the medium contact surface over time during exposure, the exposure duration, the thickness of at least two regions arranged sequentially along the medium migration direction, and at least two candidate mix proportions are obtained. Starting from the contact surface of the medium, each region is sequentially designated as the current region and the following processing is performed: Combined specimens were prepared using each candidate mix ratio; the combined specimens were cast in the order of the arrangement of the concrete layers corresponding to the current region and each region located between the current region and the medium contact surface. The thickness of each concrete layer is equal to the thickness of the corresponding area. The concrete layer in the current area adopts the corresponding candidate mix ratio, and the concrete layers located between the current area and the medium contact surface adopt the selected mix ratio of the corresponding area. Each combined specimen was cured to the initial exposure age; according to the change of medium concentration over time, a single-sided corrosion medium intrusion test was carried out on each combined specimen from the medium contact surface within the exposure duration; After the test, the penetration depth of the corrosive medium in the concrete layer of the current area of ​​each composite specimen was measured; the candidate mix proportion corresponding to the composite specimen with the smallest penetration depth was selected as the mix proportion of the current area. Output the proportions and thicknesses of each region.

2. The method for optimizing the mix proportion of corrosion-resistant concrete according to claim 1, characterized in that, Before outputting the proportions and thicknesses of the at least two regions, the current region is determined sequentially from the at least two regions in the order of moving inward from the medium contact surface along the medium migration direction, and the following processing is performed: For each candidate mix proportion, a composite specimen is prepared consisting of concrete layers corresponding to the at least two regions respectively; the thickness of each concrete layer is equal to the thickness of the corresponding region, the concrete layer of the current region adopts the candidate mix proportion, and the concrete layers of other regions except the current region adopt the selected mix proportion of the corresponding region. Each combination of specimens was cured to the stated exposure initiation age; According to the change of the medium concentration over time, a single-sided corrosion medium intrusion test is carried out on each composite specimen from the medium contact surface within the exposure time. After the test, the intrusion depth of the corrosive medium in the concrete layer of the current area of ​​each composite specimen is measured. The candidate mix ratio corresponding to the composite specimen with the smallest intrusion depth is selected to replace the selected mix ratio in the current area.

3. The method for optimizing the mix proportion of corrosion-resistant concrete according to claim 1, characterized in that, The thickness of the at least two regions is obtained in the following manner: Specimens were prepared using each candidate mix proportion, and the thickness of each specimen along the migration direction of the medium was equal to the thickness of the concrete along the migration direction of the medium. Each specimen was cured to the stated exposure initiation age; According to the change of the medium concentration over time, a single-sided corrosion medium intrusion test is carried out on each specimen within the exposure time; at least two detection times are set within the exposure time, and the intrusion depth of each specimen is measured at each detection time; The medium contact surface, the surface opposite to the medium contact surface, and the non-overlapping intrusion depth positions are defined as the region boundaries; the region boundaries are arranged along the medium migration direction, and the distance between every two adjacent region boundaries along the medium migration direction is defined as the thickness of a region.

4. The method for optimizing the mix proportion of corrosion-resistant concrete according to claim 3, characterized in that, The at least two detection times correspond to different test specimen groups, and each test specimen group includes test specimens prepared using each candidate ratio; When any detection time is reached, the single-sided corrosion medium intrusion test of the specimen group corresponding to that detection time is ended, and the intrusion depth of each specimen in the specimen group is measured. Continue to perform the single-sided corrosion medium intrusion test on each group of specimens that has not yet reached the corresponding testing time.

5. The method for optimizing the mix proportion of corrosion-resistant concrete according to claim 1, characterized in that, For each combination of specimens, a separate control specimen was prepared. The number of concrete layers in the control specimen is equal to the number of concrete layers in the corresponding composite specimen, and the mix proportion and thickness of each concrete layer in the control specimen are equal to the mix proportion and thickness of the concrete layer at the same position in the corresponding composite specimen. Each combination of specimens and its corresponding control specimens were placed in the same curing environment and cured until the exposure initiation age was stated. During the single-sided corrosion medium immersion test of each combination specimen, the corresponding control specimen was kept in the curing environment and kept out of contact with the corrosive medium. After the test, samples were continuously taken from the same position and thickness of each combined specimen and its corresponding control specimen along the direction of medium migration, and the content of corrosive medium in each sample was measured. Within the current area of ​​the concrete layer of each composite specimen, the sample with the corrosive medium content that is greater than that of the corresponding control specimen at the same location and is furthest from the medium contact surface is identified; the distance from the side of the current area of ​​the concrete layer facing the medium contact surface to the side of the sample away from the medium contact surface is taken as the penetration depth of the composite specimen in which the sample is located. When the corrosive medium content of each sample in the current area of ​​any combined specimen is not greater than the corrosive medium content of the corresponding control specimen at the same location, the penetration depth of the combined specimen is recorded as zero.

6. The method for optimizing the mix proportion of corrosion-resistant concrete according to claim 1, characterized in that, In each composite specimen, the joint surface of adjacent concrete layers is perpendicular to the direction of medium migration.

7. The method for optimizing the mix proportion of corrosion-resistant concrete according to claim 6, characterized in that, Adjacent concrete layers are poured sequentially from the contact surface of the medium inward along the migration direction of the medium, with each subsequent concrete layer poured on the surface of the previous concrete layer away from the contact surface of the medium before the previous concrete layer initially sets.

8. The method for optimizing the mix proportion of corrosion-resistant concrete according to claim 1, characterized in that, Each candidate mix corresponds to at least two combined specimens; the maximum value among the penetration depths of each combined specimen corresponding to the same candidate mix is ​​taken as the penetration depth of that candidate mix; the candidate mix with the smallest penetration depth is selected as the mix for the current region.

9. The method for optimizing the mix proportion of corrosion-resistant concrete according to claim 1, characterized in that, During the single-sided corrosive medium immersion test, the surfaces of each combined specimen except for the medium contact surface are sealed; the medium contact surface of each combined specimen is kept in continuous contact with the corrosive medium during the exposure time; the concentration of the corrosive medium in contact with the medium contact surface of each combined specimen is adjusted according to the change of the medium concentration over time.

10. The method for optimizing the mix proportion of corrosion-resistant concrete according to claim 1, characterized in that, All candidate formulations use the same types of constituent materials, but the unit volume of at least one constituent material differs between any two candidate formulations.

Citation Information

Patent Citations

  • Design method of concrete mix ratio based on requirements of index of resistance to chloride ion intrusion and strength index

    CN103992076A